Manuals for economis with work exercises - Silon, Elsa T.; Bernardo, Ramon A.; Quiloy, Melani C. (Manila, 2009)
This manual contains selected topics that need to be emphasized in a one-term basic introductory economics course. The approach is simple for the appreciation of any college students who are required to take the subject on the principles of economics. The manual guarantees a usable level of economic literacy for those students who do not go beyond the principles of economic course and a viable foundation of economic understanding for those who will pursue a course in Iconomics. Taxation, Land Reform, and Cooperative are briefly introduced in the manual.
Keywords: Economics- Examinations, questions, etc